2022
DOI: 10.1007/s10637-021-01205-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of apatinib combined with FOLFIRI in the first-line treatment of patients with metastatic colorectal cancer

Abstract: SummaryObjective. To evaluate the efficacy and safety of apatinib combined with FOLFIRI in the first-line treatment of advanced metastatic colorectal cancer (mCRC) and explore potential factors of efficacy. Methods. Twenty mCRC patients treated at Affiliated Cancer Hospital of Shanxi Medical University from March 2017 to March 2019 were included according to the enrolment criteria. They provided informed consent and were treated with apatinib combined with FOLFIRI according to the scheduled regimen until disea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Thus it was approved by the National Medical Products Administration (NMPA) of China in 2014 as an alternative anti-neoplastic drug available for patients with advanced gastric cancer or gastroesophageal junction (GEJ) carcinoma (9). Furthermore, Apatinib exhibits promising anti-tumor activities in various tumors, including hepatocellular carcinoma, breast cancer, and non-small-cell lung cancer (10)(11)(12). Additionally, Apatinib could sensitize resistant tumor cells to chemotherapy drugs meanwhile reverse the multiple drug resistance (MDR) caused by ATPbinding cassette transporters proteins (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it was approved by the National Medical Products Administration (NMPA) of China in 2014 as an alternative anti-neoplastic drug available for patients with advanced gastric cancer or gastroesophageal junction (GEJ) carcinoma (9). Furthermore, Apatinib exhibits promising anti-tumor activities in various tumors, including hepatocellular carcinoma, breast cancer, and non-small-cell lung cancer (10)(11)(12). Additionally, Apatinib could sensitize resistant tumor cells to chemotherapy drugs meanwhile reverse the multiple drug resistance (MDR) caused by ATPbinding cassette transporters proteins (13).…”
Section: Introductionmentioning
confidence: 99%
“…[28] In previous studies, apatinib was shown to have an effect on human patients who had received chemotherapy for thyroid cancer and other advanced cancers, such as gastric cancer (6.5 vs 4.7 months, P = .0149), liver cancer, colorectal cancer, and breast cancer. [29][30][31][32] It can effectively exert antitumor effects. Previous clinical studies have shown that apatinib is a viable treatment option for advanced thyroid cancer with significant efficacy in ORR, PFS, and OS, and a good safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…APA has been approved as an antineoplastic drug for advanced GC or gastroesophageal junction (GEJ) cancer in China [7]. Additionally, APA exhibits excellent anti-tumor activity in HCC [8], breast cancer [9], and CRC [10].…”
Section: Introductionmentioning
confidence: 99%